FACTORS ASSOCIATED WITH INADEQUATE MILK CONSUMPTION AMONG ADOLESCENTS: NATIONAL SCHOOL HEALTH SURVEY - PENSE 2012 - Janiquelli Barbosa Silva; Bianca Caroline Elias; Laís Amaral Mais; Sarah Warkentin; Tulio Konstantyner; Fernanda Luisa Ceragioli Oliveira (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To identify the prevalence and factors associated with inadequate milk consumption among adolescents. Methods: This was a cross-sectional study based on secondary data from the National School Health Survey (2012), a Brazilian survey carried out using a self-administered questionnaire in a representative sample of 9th-grade students from public and private schools. The frequency of milk intake and its association with socio-demographic characteristics, food consumption and physical activity were estimated. A descriptive and inferential analysis of factors associated with inadequate milk consumption (no consumption at least one of the seven days of the week) was performed. A multiple logistic model was adjusted to control confounders. Results: The sample included 108,828 adolescents and inadequate milk consumption ocurred in 58.9%. The final model included nine variables independently associated with inadequate milk intake: breakfast frequency less than 4 days per week (odds ratio [OR]=2.40; p<0.001), unprocessed or minimally processed foods intake less than 5 days per week (OR=1.93; p<0.001), living in the northeast region (OR=1.39; p<0.001), less maternal schooling (OR=1.35; p<0.001), physical inactivity (OR=1.33; p<0.001), attending public school (OR=1.26; p<0.001), not being white (OR=1.14; p<0.001), being older than 14 years old (OR=1.13; p<0.001) and having a habit of eating meals while watching TV or studying (OR=1.04; p=0.036). Conclusions: Inadequate milk consumption is prevalent among Brazilian adolescents. The identification of associated factors suggests the need to develop nutritional guidance strategies for the prevention of diseases that result from low calcium intake.